2022
DOI: 10.3389/fsurg.2022.1007883
|View full text |Cite
|
Sign up to set email alerts
|

One-and-a-half nostril versus binostril endoscopic transsphenoidal approach to the pituitary adenomas: A prospective randomized controlled trial

Abstract: BackgroundBinostril endoscopic transsphenoidal approach (BETA) is the most used approach for sellar lesions nowadays, while its damage to the nasal structures may cause nasal discomfort and affect nasal functions including respiration and olfaction. With the purpose to improve the post-operative sinonasal quality of life (QoL), we introduced the one-and-a-half nostril endoscopic transsphenoidal approach (OETA) in 2016 which preserved more natural structures and registered a prospective randomized controlled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Our team reported the OETA in 2016, which completely preserved the mucosa in the left nostril, especially the septal olfactory strip and the vascular pedicles of sphenopalatine, and reduced the risk of anosmia and epistaxis ( 9 ). The randomized controlled trial comparing the OETA and binostril approach showed that the OETA group had better olfaction function than the binostril group one month after surgery ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our team reported the OETA in 2016, which completely preserved the mucosa in the left nostril, especially the septal olfactory strip and the vascular pedicles of sphenopalatine, and reduced the risk of anosmia and epistaxis ( 9 ). The randomized controlled trial comparing the OETA and binostril approach showed that the OETA group had better olfaction function than the binostril group one month after surgery ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, our team proposed the one-and-a-half (1½) nostril endoscopic transsphenoidal approach (OETA) which maintains sufficient surgical freedom and retains as much nasal septal mucosa as possible ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%